ANALISIS KINERJA PENGELOLAAN ADMINISTRASI KEUANGAN DI SAHID RAYA HOTEL & CONVENTION YOGYAKARTA - Masrukhan, M.; Lita, Viola Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the financial administration performance at Sahid Raya Hotel & Convention Yogyakarta, focusing on operational efficiency, challenges, and the role of information technology in financial management. A qualitative approach with descriptive analysis was employed. Data were collected through in-depth interviews, observations, and document analysis. The findings indicate that a well-structured financial administration system contributes to the hotel’s operational efficiency. However, challenges such as revenue fluctuations and limited financial literacy among staff still affect financial performance. The implementation of information technology, such as online reservations and digital payment systems, has proven to enhance efficiency and customer satisfaction. This study provides strategic recommendations to address challenges and optimize financial management